Indicators Framework for the Influence of Political Power in Building an Image of Architecture, Case Study: The Government Buildings - Ghada Ragheb; Naira Zaky; Aisha Awad; Alaa El-Deghady; Horuyra Ismaiel; Sherif Hosni; Maha Abd El-Wahab (Recent Trends in Arts and Social Studies Vol. 5, 2023)
Political power is a significant factor in the ideological and intellectual change of architectural production. This article aims to determine the impact of the state’s political ideology on shaping architecture in different countries. In this context, the manuscript is concerned with reviewing the previous literature on the essential indicator concept of political power and its impact on shaping the image of architecture according to the rules, patterns, and traditions of society. This study achieved a proposed framework for indicators that are easy to apply on several international and Arab governmental buildings to reflect the role of the authority in building the architectural image and identity of those buildings and their reflection on the city. This paper adopts a qualitative research strategy based on the case study methodology. The test of criteria derived from the theoretical framework includes examining the symbolic meanings embodied in the physical characteristics of a sample of selected Arab and international government buildings. The results show how the country’s culture and the time factor affected the way symbolism is displayed and how government buildings worked as a social and political tool to set a new form for the relationship between architecture, power, and the people through an insight into the political and cultural role of architecture. The research recommends the importance of investing in the local heritage and the capabilities of advanced technology as a basis for expressing the influence of the political authority in building a clear architectural image of the buildings and the city, As well as focusing on finding the symbolic aspect in parallel with finding the form to create images that evoke the feelings of the recipient, which reflect positively on the knowledge of the ruler and the people about the importance of those inherited values.